Marketing Strategy for Home Ownership Financing (PPR) Products at Bank BJB Syariah KCP Indramayu - Meida Tisnawati Putri (Konsultan Jurnal Ilmiah Indonesia, 2025)
Financial services are an essential part of the modern economy, including the banking sector, which plays a vital role in supporting economic development. In the Islamic economic system, the significance of Islamic banking has grown rapidly along with increasing public awareness of Sharia-based financial principles. Bank BJB Syariah KCP Indramayu, one of the Islamic banks in Indonesia, supports government programs through subsidized Sharia-based Home Financing (PPR) products. These products aim to assist low-income communities (MBR) in obtaining proper housing through Sharia contracts such as Murabaha, Musharakah Mutanaqisah, and Ijarah Muntahiyah Bi Tamlik. This study aims to explore the marketing strategies employed by Bank BJB Syariah KCP Indramayu to increase public interest in subsidized Sharia-based PPR products. A qualitative approach was used to collect data through interviews and direct observations at the research site. The results indicate that the marketing strategies implemented include utilizing customer data for personalized offers, conducting the